TINGKAT PENGETAHUAN DAN TINGKAT KONSUMSI SAYUR BUAH PADA REMAJA DI SMP NEGERI 2 DENPASAR - I Gede Putu Satria Wibawa; Desak Putu Sukraniti; I Made Suarjana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
The results of Riskesdas in 2018 showed that 95.5% of Indonesia's population aged five years and over consume less vegetable and fruit than 5 portions a day. This study was an observational study with a sample of 104 teenagers. The results of this study indicate that the majority of teenagers in SMP Negeri 2 Denpasar have sufficient knowledge of 52.0%. The level of consumption of teenage vegetable a day all included in the category of less than 100% and the level of consumption of fruit a day of teenagers mostly included in the category of less than 64.4%. Distribution of vegetable consumption level based on the knowledge level that all adolescents are 100% with less vegetable consumption level most have enough knowledge of 52.0%. The distribution of juvenile fruit consumption level based on the knowledge level is 37 people (35.6%) with sufficient fruit consumption level most have good knowledge 89.2%, and as many as 67 people (64.4%) with less fruit consumption level most have sufficient knowledge 74.6%. There is no tendency between the knowledge level with the consumption of vegetable in adolescents, where adolescents with good knowledge are not followed by adequate vegetable consumption, while there is a tendency between the knowledge level with fruit consumption in adolescents, where adolescents with good knowledge followed by sufficient fruit consumption. It is recommended that teenagers ask their parents to provide vegetable and fruit in the family menu every day. Schools need to create programs that support students to consume vegetable and fruit.Keywords: knowledge, consumption vegetable and fruit.